Minamata [videorecording (DVD)] - Depp, Johnny; Sanada, Hiroyuki, 1960-; Kunimura, Jun; Minami; Kase, Ryō, 1974-; Asano, Tadanobu; Iwase, Akiko; Nighy, Bill, 1949-; Smith, Aileen Mioko (Samuel Goldwyn Films, 2022)
About a celebrated war photographer W. Eugene Smith in a real life David vs Goliath story, pitting Smith against a powerful corporation responsible for poisoning the people of Minamata, Japan in 1971. With the glory days of World War II far behind him, Smith has become a recluse. Between an impassioned Japanese translator called Aileen urging him to go and a much-needed commission from "Life" Magazine editor Ralph Graves, Smith is finally convinced to journey back to Japan to expose the devastating annihilation of a coastal community, victims of corporate greed and complicit local police and government. Armed with only his trusted Nikon camera, Smith must find the images that will bring this story to the World. MINAMATA is a moving redemptive story of how one man's powerful photograph impacted the world, yet to find it he had to open his heart.